2021
DOI: 10.1007/s40520-021-02021-8
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and in-hospital mortality: retrospective analysis of a nationwide administrative database of elderly subjects in Italy

Abstract: Aims To evaluate the relationship between comorbidity and in-hospital mortality in elderly patients affected by dementia. Methods Data were obtained from the Italian Ministry of Health and included all discharge records from Italian hospitals concerning subjects aged ≥ 65 years admitted to acute Internal Medicine or Geriatrics wards between January 2015 and December 2016 (3.695.278 admissions). The variables analyzed included age, sex, and in-hospital death. Twenty-five homogeneous clusters of diseases were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In an analysis of 3.7 million hospitalizations of adults ≥65 years of age throughout Italy, of whom 278 149 were patients diagnosed with dementia, those with dementia were more likely to die while in the hospital than those without dementia (age-, sex-, and comorbidity-adjusted OR, 1.98 [95% CI, 1.95−2.00]). 216 Among patients with dementia, the comorbidities most strongly associated with higher risk for in-hospital mortality were HF, pneumonia, and kidney disease.…”
Section: Brain Healthmentioning
confidence: 99%
“…In an analysis of 3.7 million hospitalizations of adults ≥65 years of age throughout Italy, of whom 278 149 were patients diagnosed with dementia, those with dementia were more likely to die while in the hospital than those without dementia (age-, sex-, and comorbidity-adjusted OR, 1.98 [95% CI, 1.95−2.00]). 216 Among patients with dementia, the comorbidities most strongly associated with higher risk for in-hospital mortality were HF, pneumonia, and kidney disease.…”
Section: Brain Healthmentioning
confidence: 99%
“…Dementia is the fifth non-communicable cause of death globally, and the second cause in high-income countries [ 5 ]. It significantly increases in-hospital mortality among older subjects [ 6 ]. However, at present, there is limited, if any disease-modifying treatment, with the result that the burden of dementia, and particularly AD is likely to continue growing.…”
Section: Infectious-related Dementia: 30 Years Of Controversymentioning
confidence: 99%
“…These results were in line with a cross-sectional study of patients aged 65 and older in randomly selected general hospitals in Germany [4], confirming that 40% of patients older than 65 years of age had mild cognitive impairment or dementia. These patients were more often treated for dehydration, electrolyte disturbances, urinary tract infections, contusions, and bone fractures, as well as for symptoms and findings of an unknown nature [5]. Over the last two decades, Blandi et al [6] observed an increased mortality among PlwD admitted to hospital.…”
Section: Introductionmentioning
confidence: 99%